Non-governmental organizations, the state and the politics of rural development in Kenya with particular reference to Western Province - Matanga, Frank Khachina (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2002)
In recent decades, Non-Governmental Organizations (NGOs) have increasingly taken on development and political roles in Africa. This has partly been attributed to the New Policy Agenda (NPA) mounted by the international donors. The NPA is predicated on neo-liberal thinking advocating for an enlarged development role for the private sector and a minimalist state. This relatively new shift in development thought has been motivated by the declining capacity of the African state to deliver development and guarantee a liberal political system. This study, therefore, set out to empirically examine whether NGOs are capable of effectively playing their new-found development and political roles. The study was based on Kenya with the Western Province constituting the core research area. The fact that the Kenyan state has been gradually disengaging from the development process has created a vacuum of which the NGOs have attempted to fill. Equally important has been the observation that, for the greater part of the post-colonial period, the state has been largely authoritarian and therefore prompting a segment of civil society to take on political roles in an effort to force it to liberalize and democratize. Urban NGOs in particular, have been the most confrontational to the state with some remarkable success. Unlike their urban counterparts, rural-based NGOs have tended to be more developmental and play a politics of collaboration with the state. Many of the latter NGOs, although playing a significant role in rural development, have been co-opted into patron-client networks. Factors that influence NGOs= posture towards the state include the nature of their leadership, the extent of their nternational connections, and the level of resources at their disposal. The study=s principal conclusion, is that, in as much as NGOs and overall civil society have provided a basis for development and opposition to the state, there is an urgent and growing need for them to shift from a position of dependency, whether domestic or international, to relative autonomy. Only then, will their contributions be sustainable in society.
Keywords: Non-governmental organizations -- Kenya; Rural development -- Kenya